Epidemiologic surveillance of diseases outbreaks transmitted by foods in Santiago de Cuba province - Arístides Ramón Rodríguez Julian; Mayelin Marin Mendez; Laidelbis Minier Pouyou; Ilia De la Caridad. Rizo Arredondo; Yayma Fuentes Gómez (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: Diseases transmitted by foods take place due to the ingestion of foods and/or contaminated drinks.   Objective: To identify the causal agents that influence in the emergence of these diseases.  Methods: An observational, descriptive and cross-sectional study of all the diseases outbreaks transmitted by foods was carried out in Santiago de Cuba, from January, 2018 to December, 2019. The analyzed variables were: number of outbreaks, samples of foods and samples of stools for coproculture, among others.   Results: In all the outbreaks a single type of bacterial agent was isolated, with prevalence of the gram-negative bacterias, where Salmonella was the most identified microorganism. The main groups of foods related to the emergence of these outbreaks were  meat and its derived products, as well as  cold salad.   Conclusions: The epidemiologic surveillance of diseases outbreaks transmitted by foods, allowed to identify the true causal agent in the FTD outbreaks, when the identity between the bacterial isolations obtained from samples of foods and stools was demonstrated.